URGENSI PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER BANGSA - Fachri, Moh. (JURNAL AT-TURAS, 2014)
Character or disposition is personality shape which applies into morality value and contains in every person side that based on thinking, attitude, and behavior. A character is formed by intensive effort, step by step continuity, in order to get maximum yield. similarly the nation character, has to effort seriously for their character building. Education is a right medium and strategy for nation character building. Seeing that in education side, students are guided, and taught from mentality, emotional, intellectual, attitude, behavior, speaking etc until they get best personality. Islamic education as part of student character building effort has an urgent and strategic role to get nation character building. In Islamic education, students aren’t studying in Islamic studies only but they are also taught to comprehend fully and apply Islamic value as they know everyday, as individual  person or Indonesian Society.